Sobre el concepte de realisme i realisme històric - Broch, Àlex (Caplletra. Revista Internacional de Filologia, 2000)
Resum: Starting from the relationship between literature and reality, this essay provides a reflection of the concept of realism and its different understandings and positionings in contemporary literature. A revisión of realism in the 19th and 20th centúries leads one, on the first hand, to the 1Oth-century idea of realism which witnessed the process of transformation and change in modern society; and on the other hand, to 20th-century socialist realism, a functionalist conception of art and literature which has to reflect the historical moment. Finally, and in relation to Catalan literature, this essay analyzes the historical realism of the 1960s. Paraules clau: realisme; literatura catalana contemporània; realisme històric